2022
DOI: 10.5935/1806-6690.20220025
|View full text |Cite
|
Sign up to set email alerts
|

Potassium silicate as an inducer of abiotic stress resistance in grain sorghum seeds

Paloma Rayane Pinheiro,
Charles Lobo Pinheiro,
Luma Rayane de Lima Nunes
et al.

Abstract: Sorghum is an important crop that can absorb and accumulate abundant Si ranging, improving tissue tolerance to the water and salt stress and reducing sodium absorption. T hus, the objective was to verify the induction of resistance in germination and seedling growth of sorghum seeds to salt and water stress during germination due to treatment with silicon. Two experiments were carried out with seeds of two sorghum cultivars (EA03 and EA955) were solution of potassium silicate solutions at concentrations of 0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The ~10% growth and biomass gain with silicon are due to its positive effects on plant tissue. According to Pinheiro et al (2022), sorghum can absorb and accumulate Si in abundance, improving its tolerance to salt stress. The greater the Si accumulation in tissue, the more benefits can be observed in reducing the damage caused by salt stress in plants, as reported by Migliorini et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…The ~10% growth and biomass gain with silicon are due to its positive effects on plant tissue. According to Pinheiro et al (2022), sorghum can absorb and accumulate Si in abundance, improving its tolerance to salt stress. The greater the Si accumulation in tissue, the more benefits can be observed in reducing the damage caused by salt stress in plants, as reported by Migliorini et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…The exogenous application of Si has been considered an eco-friendly practice [10], which maintains an optimal K + /Na + ratio and nutrient balance and regulates the production of reactive oxygen species (ROS) [11], as well as increases the activity of H + -ATPase in the plasma membrane and tonoplast, facilitating the extrusion of Na + from the cell [12]. Several studies have reported the effectiveness of Si in mitigating salt stress in different crops [13,14], such as quinoa (Chenopodium quinoa Willd.) [15], which is a promising crop for semiarid regions because it is known to be tolerant to water and saline stress [16] and is an important food source due to its high nutritional value [17].…”
Section: Introductionmentioning
confidence: 99%